Development of Video Media on Reptilian and Aves Biodiversity at Ragunan Zoo - Adinugraha, Fajar; Sembiring, Geskia Avikasari; Olivia S, Frisca; Selvina, Junata; Angela, Ezra; Hutabarat, Anne Serafin; Situmorang, Agnes Feronika (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2024)
The decline in biodiversity and lack of knowledge among young people regarding Reptilia or reptiles and Aves or birds are pressing issues that require attention. To address this, an educational video has been created to provide information on various species of reptiles and birds. Field research was conducted at Ragunan Zoo to gather data on these species, which was then used to produce the educational video. The exploration results reveal the classification of 17 species of Reptilia into three orders: Crocodilia, Squamata, and Testudines. A video on Reptilia is available on YouTube at https://youtu.be/NT5GOaZXmdQ. The video has a duration of 16 minutes and 44 seconds. Observations at Ragunan Zoo revealed the presence of 12 Aves species from 10 orders: Galliformes, Gruiformes, Phoenicopteriformes, Bucerotiformes, Ciconiiformes, Columbiformes, Falconiformes, Psittaciformes, Struthioniformes, and Pelecaniformes. A video about Aves is available on YouTube at https://youtu.be/aUGOXCsspmM, with a duration of 11 minutes and 47 seconds. Educational videos that feature native animals and species can help viewers gain a better understanding of animal diversity, particularly Reptilia and Aves. This increased understanding of biodiversity, including different species, can help raise awareness of the importance of preserving biodiversity.